2014
DOI: 10.1017/sjp.2014.1
|View full text |Cite
|
Sign up to set email alerts
|

Early Maladaptive Schemas and Personality Disorder Traits in Perpetrators of Intimate Partner Violence

Abstract: Abstract. Personality disorders (PDs) are highly prevalent among perpetrators of intimate partner violence (IPV). Schema Therapy proposes a number of early maladaptive schemas (EMSs) that are involved in the development of PDs. This study examined the prevalence of PD traits in a sample of men who committed violence against their partners and the relationship between EMSs domains and PD traits. With this aim, a sample of 119 convicted men completed the Young Schema Questionnaire-Short Form (YSQ-SF; Young & Bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 58 publications
2
17
2
1
Order By: Relevance
“…Also, these findings are in line with predictions of the SFCT with regards to personality disorders (Karp & Dugas, 2003;Seavey & Moore, 2012;Young, 1990;Young & Klosko, 2005;Young, Klosko, & Weishaar, volume 5(4),  Table 3 Tests of between-subjects effect of group status and gender interaction in maladaptive schemas Dependents 2003). While previous literature supported the role of EMSs in interpersonal problems and personality disorders, particularly borderline and antisocial personality disorders (Arntz, 2010;Arntz, Klokman, & Sieswerda, 2005;Arntz & van Genderen, 2009;Corral & Calvete, 2014;Gullhaugen & Nøttestad, 2012;Thimm, 2013;Özdel et al, 2015), the present findings show the importance of EMSs in emergence of the full range of cluster B personality disorders. Therefore, EMSs could be considered as important susceptibility factors for the development of some personality disorders, particularly the cluster B personality disorders.…”
Section: Discussioncontrasting
confidence: 50%
“…Also, these findings are in line with predictions of the SFCT with regards to personality disorders (Karp & Dugas, 2003;Seavey & Moore, 2012;Young, 1990;Young & Klosko, 2005;Young, Klosko, & Weishaar, volume 5(4),  Table 3 Tests of between-subjects effect of group status and gender interaction in maladaptive schemas Dependents 2003). While previous literature supported the role of EMSs in interpersonal problems and personality disorders, particularly borderline and antisocial personality disorders (Arntz, 2010;Arntz, Klokman, & Sieswerda, 2005;Arntz & van Genderen, 2009;Corral & Calvete, 2014;Gullhaugen & Nøttestad, 2012;Thimm, 2013;Özdel et al, 2015), the present findings show the importance of EMSs in emergence of the full range of cluster B personality disorders. Therefore, EMSs could be considered as important susceptibility factors for the development of some personality disorders, particularly the cluster B personality disorders.…”
Section: Discussioncontrasting
confidence: 50%
“…Regarding this issue, Young (1999) first proposed that several EMSs were particularly central to BPD, including those related to abandonment, dependence, mistrust, abuse, subjugation, emotional deprivation, and insufficient self-discipline. In addition, several empirical studies have shown sound evidence for the relationship between the intensity of EMSs and BPD severity, in both clinical and nonclinical populations (Ball & Cecero, 2001;Corral & Calvete, 2014;Meyer, Leung, Feary, & Mann, 2001;Sajadi, Arshadi, Zargar, Mehrabizade Honarmand, & Hajjari, 2015;Shorey, Anderson, & Stuart, 2014;Specht, Chapman, & Cellucci, 2009;Taylor & Reeves, 2007). Despite this progress, it remains unclear whether EMSs are directly associated with relevant aspects of dimensional psychopathology in BPD, such as internalizing symptoms, psychotic-like symptoms, suicidal ideation, or aggressiveness, which could provide a more comprehensive framework on the overall influence of EMSs on people with BPD (Black, Blum, Pfohl, & Hale, 2004;Látalová & Prasko, 2010;Lee, Allen, Black, Zanarini, & Schulz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An earlier research conducted by Estevez et al revealed a positive association between VAW and the 5 EMSs with higher rations of the disconnection/rejection and the impaired autonomy domains 9,11 . The disconnection/rejection domain involves schemes which indicate that one's safety, empathy, nurturance, recognition and respect needs will not be met 27 . Three schemas were found to be associated with violence: first, the emotional deprivation schema in which a women sense that other individuals are unable to provide the love and care she needs, may join cold and abusive individuals with little affection; the second one is the defectiveness schema in which a women have expectations of being rejected and abused by others could result in women appearing weak and becoming a more probable target of abuse in intimate relations ; the third one is social isolation schema in which a women feel isolated from other people 6 .…”
Section: Discussionmentioning
confidence: 99%